Fraternity in the Encyclical Fratelli Tutti: Franciscan roots - Carbajo Núñez, Martín (Revista Eclesiástica Brasileira, 2021)
This article studies the subject of fraternity in the encyclical Fratelli tutti and explores its Franciscan roots. The Pope asserts that “it was the evangelical witness of St. Francis, with his school of thought, that gave this term the meaning it then preserved over the centuries.” The key to understand it is found in the encounter with the needy (leper, wounded), which brings to light the dignity of each human person and the need for social friendship in order to achieve a “healthy and open” community life. Síntese: O presente artigo estuda o tema da fraternidade na encíclica Fratelli tutti e evidencia alguns pontos de contato com a perspectiva franciscana. O Papa afirma que “foi o testemunho evangélico de São Francisco, com sua escola de pensamento, que deu ao termo fraternidade o significado que este conservou no decorrer dos séculos”. O artigo explora estas raízes franciscanas. A chave de leitura encontra-se no encontro com o necessitado (leproso, ferido), que evidencia a dignidade de toda pessoa humana e a necessidade da amizade para alcançar uma vida social “sadia e aberta”.